Antibodies to citrullinated peptides are not associated with the rate of joint destruction in patients with a well-established diagnosis of rheumatoid arthritis - Nieto-Colonia, Alberto Max [UNIFESP] (2008)
Antibodies to citrullinated peptides are highly specific for rheumatoid arthritis (RA) and represent a significant risk factor for undifferentiated polyarthritis. This prognostic ability may be related to the very diagnostic performance of these autoantibodies, since RA is a more erosive disease than other forms of arthritis. The present study evaluated an association of antibodies to citrullinated peptides and the rate of joint destruction in patients with a well-established diagnosis of RA. Seventy-one patients with RA were evaluated in 1994 and again in 2002 (functional class, joint count, Health Assessment Questionnaire score, hands X-ray). Autoantibodies (rheumatoid factor (RF), anti-perinuclear factor, anti-cyclic citrullinated peptide (CCP) antibodies) and Sharp's index were analyzed blindly. Delta Sharp was calculated as the difference in Sharp's index obtained in 1994 and 2002. During the follow-up the Health Assessment Questionnaire score increased from 0.91 ± 0.74 to 1.39 ± 0.72 (P < 0.001). Similarly, the number of swollen joints increased from 4.6 ± 5.71 to 6.4 ± 4.1 (P = 0.002). The frequency of autoantibodies and anti-CCP titer remained stable; however, serum RF concentration increased from 202.8 ± 357.6 to 416.6 ± 636.5 IU/mL (P = 0.003). Sharp's index increased from 56.7 ± 62.1 to 92.4 ± 80.9 (P < 0.001). No correlation was observed between Delta Sharp and the presence of RF, anti-perinuclear factor, and anti-CCP antibodies at baseline. Antibodies to citrullinated epitopes are specific and early markers for the diagnosis of RA but do not seem to be associated with the rate of joint destruction in patients with a well-established diagnosis of RA.